Novel concepts for the biocatalytic synthesis of second-generation biodiesel - Spanou, Androniki; Moschona, Alexandra; Theodosiou, Eleni; Patsios, Sotiris I.; Pavlidis, Ioannis V. (Frontiers in Catalysis, 2024)
Biodiesel is synthesized by the transesterification of triglycerides of oils with short-chain alcohols, such as methanol and ethanol. According to the Renewable Energy Directive guidelines (RED II 2018/2001/EU) the contribution of advanced biofuels, which do not include edible oils, towards the overall EU target, is at 1% in 2025% and at least 3.5% in 2030. Bioprocesses that valorize non-edible oils for the production of second-generation biodiesel could play a critical role in achieving this goal. Immobilized lipases, as well as other enzyme classes, such as cutinases and acyltransferases, are utilized as biocatalysts for this process. For the sustainability of the process, renewable materials can be used as immobilization matrices, or even enzymes anchored on the cells, as whole-cell biocatalysts. Membrane reactors can also be employed to facilitate the enzymatic transesterification by conducting a continuous enzymatic reaction and simultaneously separate the products in a single operation. The advances on the aforementioned fast-pacing fields are presented in this work.